(untitled) (Gestión y Gerencia, 2024)
This research partially demonstrates the validity of Okun’s law in the Bolivarian Republic of Venezuela, 2000 to 2021, convulsive period.The law states that for every 1% increase in the unemployment rate above the natural unemployment rate of 6%, 3% of the value of real Gross Domestic Product (GDP) would no longer be produced. The study is of an explanatory, correlational nature, with longitudinal data. It shows compliance with Okun’s postulate in the global period, having stopped producing on average 4.89% of real GDP, with two dissimilar behaviors: from 2000 to 2006, the average potential loss of real GDP was 11.08% due to not reaching full employment, while from 2007 to 2021 an average of less than the normative gap of 3% of real GDP was lost. It concludes: The full use of production factors could not be verified, although it is close to the country’s productive potential by relating the unemployment rate to the GDP. Finally, it is suggested to decree monetary and financial policies that strengthen the business sector to increase the level of national production.